2019
DOI: 10.1080/1059924x.2019.1567423
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Symptoms among Loggers in the Ark-La-Tex Region

Abstract: Background: The U.S. logging sector is among the most dangerous industrial sectors, with high fatality and non-fatal injury rates. Limited research has addressed work-related musculoskeletal disorders among logging machine operators (LMOs). The purpose of this study was to estimate the 12-month prevalence of musculoskeletal symptoms and the associated work-related risk factors among LMOs in the Arkansas, Louisiana, and Texas (Ark-La-Tex) logging region.Methods: A self-administered 93-item questionnaire with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Several studies have shown that high Body Mass Index (BMI) is a risk factor for work-related muskuloskeletal disorders (WRMSDs) involving any area of the body. This observation was echoed with a group of loggers in the Ark-La-Tex region, also linking the occurrence of symptoms to high BMI [ 63 ]. However, researchers evaluating the prevalence of these symptoms among fishermen did not support such an association [ 64 ].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that high Body Mass Index (BMI) is a risk factor for work-related muskuloskeletal disorders (WRMSDs) involving any area of the body. This observation was echoed with a group of loggers in the Ark-La-Tex region, also linking the occurrence of symptoms to high BMI [ 63 ]. However, researchers evaluating the prevalence of these symptoms among fishermen did not support such an association [ 64 ].…”
Section: Discussionmentioning
confidence: 97%
“…Regarding occupation, we found an increased prevalence of self-reported LBP among agricultural/forestry/ fishery workers in both genders. In countries other than Japan, many researchers have reported that agricultural/ forestry/fishery workers are at high-risk of occupational LBP [13,25,26]. However, the subjects of previous studies have often been limited to males, and gender differences in occupational LBP among agricultural/forestry/ fishery workers have not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are not captured in the industrial accident statistics. Risk factors for LBP in agriculture/forestry/fishery Table 4 PRs (95% CIs) for self-reported LBP according to occupational class variables in 35,870 women CI confidence interval, LBP low back pain, PR prevalence ratio a Adjusted for age (per 5-year increase), marital status, family size, housing tenure, equivalent household expenditures, education, alcohol intake, smoking status, sleep duration, and chronic medical conditions b In addition to model 2, all three items of occupational class variables were included (i.e., Model 3 was mutually adjusted for all occupational class variables) workers include physical exposures (e.g., heavy lifting, hard physical work, whole-body/hand-arm vibrations, and awkward postures) and environmental exposures such as extreme cold or heat [25,26]. It is urgently necessary to take measures against LBP in agricultural/forestry/fishery workers in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, awkward and cramped conditions were noted as an adverse exposure for lower extremities as well. 4 Studies worldwide have examined the health consequences that arise from spending excessive sedentary periods inside a cramped logging equipment cab. 5,6 A Slovakian study focused on work-related factors straining the cardiovascular system found that operators' height, machine types, parts of the shifts, equivalent noise, lighting, and whole-body vibrations explained about 72% of the elevated heart rate variability.…”
Section: Introductionmentioning
confidence: 99%